The Winter Missal of Arnold of Rummen : Huis van het boek, Ms. 10 A 14 - Watson, Carolyn Coker Joslin, (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2025)
The Hundred Years' War, the Plague, the van Artevelde uprising, conflict between a count and an aspiring count, Corpus Christi and the Eucharist--these are the context for the enigmatic manuscript studied in this book. Above all, this missal from Ghent is outstanding for its rich and inventive penwork flourishing, given life by the prayer-pulses of the text and enriched by cycles of development. The lowly two-line initial emerges as the primary locus of creative interaction between painting and flourishing. Illumination, produced by a priest and a layman, is notable for its theological richness and is enlivened by distinctive gorgons.